2022
DOI: 10.7759/cureus.27645
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Infant-Feeding Presentations at English Emergency Departments During the SARS-CoV-2 Pandemic: A Nation-Wide Electronic Health Records Study

Abstract: Objectives: To examine the frequency and distribution of infant feeding-related presentations at emergency departments (EDs) before and during the SARS-CoV-2 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While some studies suggest that the frequency of overall post-discharge newborn rehospitalization did not change during the pandemic [28,29], there have been reports of increased rehospitalization risk in some subgroups such as those born to nulliparous mothers [30] and those readmitted for hyperbilirubinemia [31]. One nation-wide study from England found that while acute care presentations decreased by 16.7% overall during vs. before the pandemic, attendance for feeding problems and neonatal jaundice increased by 7.5% and 12.8% respectively [32]. Such presentations may -in particular -rely on in-person primary care assessment to help prevent poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies suggest that the frequency of overall post-discharge newborn rehospitalization did not change during the pandemic [28,29], there have been reports of increased rehospitalization risk in some subgroups such as those born to nulliparous mothers [30] and those readmitted for hyperbilirubinemia [31]. One nation-wide study from England found that while acute care presentations decreased by 16.7% overall during vs. before the pandemic, attendance for feeding problems and neonatal jaundice increased by 7.5% and 12.8% respectively [32]. Such presentations may -in particular -rely on in-person primary care assessment to help prevent poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While data on breastfeeding difficulties were not collected in the NMS, loss of full breastfeeding at 6 weeks may reflect unresolved feeding difficulties and maternal confidence [28,29]. Routine data for England showed a 7.5% increase in emergency department attendance for feeding problems in infants during the pandemic, including a 12.8% increase for neonatal jaundice [30]. In addition, we observed an increase in the prevalence of postnatal anxiety and depression in the NMS [6] and similar increases have been found in other studies [31,32].…”
Section: Plos Onementioning
confidence: 99%